2019
DOI: 10.1097/md.0000000000016156
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and pregnancy outcomes of new onset epilepsy during pregnancy

Abstract: The occurrence of seizures during pregnancy is really a challenging situation which risks the health of both mothers and fetuses. However, new onset epilepsy is unpredictable in pregnancy, and its clinic feature is barely known. This study aimed to explore the clinical characteristics and pregnancy outcomes of new onset epilepsy during pregnancy. We screened consecutive women with epilepsy and reproductive history from June 2013 to November 2018 from 3 hospitals in West China. Detailed demographics,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 15 publications
2
9
1
Order By: Relevance
“…As for the epilepsy and seizure type in pregnancy, in our study focal epilepsy and tonic-clonic seizures (both bilateral and generalized) were more common. This finding is in good agreement with the report by Li et al [33] showed that most patients (59.1%) suffered primary or secondary generalized tonic-clonic seizures. As for the time of occurrence of the first seizures, the pregnancy period of the first seizures was different, including 6 in the first trimester, 4 in the second trimester and 2 in the third trimester.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…As for the epilepsy and seizure type in pregnancy, in our study focal epilepsy and tonic-clonic seizures (both bilateral and generalized) were more common. This finding is in good agreement with the report by Li et al [33] showed that most patients (59.1%) suffered primary or secondary generalized tonic-clonic seizures. As for the time of occurrence of the first seizures, the pregnancy period of the first seizures was different, including 6 in the first trimester, 4 in the second trimester and 2 in the third trimester.…”
Section: Discussionsupporting
confidence: 93%
“…As for the time of occurrence of the first seizures, the pregnancy period of the first seizures was different, including 6 in the first trimester, 4 in the second trimester and 2 in the third trimester. This finding is not in line with report by Li et al showed that new-onset epilepsy occurred mostly in the second and third trimester [33].…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…Three of these twenty-two (16.7%) women had positive neuroimaging findings on their MRI examinations, and none had brain tumours [5]. In at least 50% of the new epileptic cases during pregnancy, EEG examination shows no signs of epileptic activity, as in our presented case [4].…”
Section: Discussionmentioning
confidence: 51%